CONSUMERS’ DECISION TO SELECT A WEDDING ORGANIZING COMPANY IN MUEANG DISTRICT NONTHABURI PROVINCE - Timdee, Nattapat; srisatanon, pornpana; Ngamkana, Prapaswat; Loppananusorn, Songpol (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were 1) to compare the decision in preferring the service of a wedding organizing company of consumers in Muang District, Nonthaburi Province. Classified by personal factor 2) to study the service marketing mix affecting the decision to prefer the service of a wedding organizing company. The sample group represents 385 consumers. Used a questionnaire tool to collect data. Statistics used in data analysis represent mean, standard deviation, t-test, F-Test, and multiple regression analysis. The research results revealed as follows: 1) The difference of consumers’ education level. and occupations, there was statistically significant different decision to prefer the service of a wedding organizing company at the 0.05 level. 2) The marketing mix consists of product aspect, price aspect location/distribution channel, marketing promotion, physical evident aspect and process affecting the decision to prefer the service of a wedding organizing company and all 6 factors could describe the variation of the decision to prefer the service of a wedding organizing company 74.90 percent